Prevention and treatment of natural products from Traditional Chinese Medicine in depression: Potential targets and mechanisms of action - He, Ming-Chao; Feng, Rui; Wang, Jing; Xia, Shi-Hui; Wang, Yong-Jun; Zhang, Yan (Frontiers in Aging Neuroscience, 2022)
The molecular pathology involved in the development of depression is complex. Many signaling pathways and transcription factors have been demonstrated to display crucial roles in the process of depression occurrence and development. The multi-components and multi-targets of Traditional Chinese Medicine (TCM) are uniquely advantageous in the prevention and treatment of chronic diseases. This review summarizes the pharmacological regulations of natural products from TCM in the prevention and treatment of depression from the aspects of transcription factors (CREB, NF-κB, Nrf2) and molecular signaling pathways (BDNF-TrkB, MAPK, GSK-3β, TLR-4).